Hindi Diwas Development of Scientific Terminology and Indian Languages - Kumar, Harish (Indian Farming, 2018)
Development of scientific words is critical for describing the new inventions/discoveries resulting from the advancement of science. The development of scientific terminologies has a long history and many international languages played a prominent role in it. Present article discussed the role of Indian languages including Sanskrit, Hindi and other regional languages in the development of scientific terminologies right from British period.